The Molecular Signature More Than the Site of Localization Defines the Origin of the Malignancy - Matrone, Antonio; Torregrossa, Liborio; Sensi, Elisa; Cappellani, Daniele; Baronti, Walter; Ciampi, Raffaele; Molinaro, Eleonora; Ugolini, Clara; Aghababyan, Aleksandr; De Napoli, Luigi; Latrofa, Francesco; Materazzi, Gabriele; et al. (Frontiers in Oncology, 2019)
The diagnosis of the primary origin of metastases to the thyroid gland is not easy, in particular in case of concomitant lung adenocarcinoma which shares several immunophenotypical features. Although rare, these tumors should be completely characterized in order to set up specific therapies. This is the case of a 64-years-old woman referred to our institution for a very advanced neoplastic disease diagnosed both as poorly differentiated/anaplastic thyroid cancer (PDTC/ATC) for the huge involvement of the neck and concomitant lung adenocarcinoma (LA). Neither the clinical features and the imaging evaluation nor the tumor markers allowed a well-defined diagnosis. Moreover, the histologic features of the thyroid and lung biopsies confirmed the synchronous occurrence of two different tumors. The molecular analysis showed a c.34G>T (p.G121C) mutation in the codon 12 of K-RAS gene, in both tissues. Since this mutation is highly prevalent in LA and very rare in PDTC/ATC the lung origin of the malignancy was documented, and the patient was addressed to the correct therapeutic strategy.